Predation on neotropical lizards Tropidurus sp. by tamarin primate Leontocebus weddelli in Brazil - Fernandes, Janayne Cristina Gomes; Paz, Matheus de Araújo; Pommer-Barbosa, Raul Afonso; Oliveira, Marcela Alvares (Therya Notes, 2023)
The diet of tamarin primates is predominantly frugivorous and insectivorous; it may include other elements in its diet such as nectar, seeds and arthropods, while vertebrate consumption is occasional. We present an unpublished record of the consumption of neotropical lizards (Tropidurus sp.) by the tamarin pichico (Leontocebus weddelli) in Porto Velho, Rondônia, Brazil. The record was conducted in 2022 at the José Ribeiro Filho campus of the Federal University of Rondônia, which is located in the peri-urban area, 9.5 km from the city of Porto Velho. The ad libitum method was used, continuously recording all important behavioral aspects of the primate. An adult individual of undetermined sex of Leontocebus weddelli was observed on the ground, completely consuming an adult individual of Tropidurus sp. for approximately 6 minutes. Representatives of the genus Leontocebus consume fruits and insects, and lizards are not the main items in their diet but represent an important energy source. This note reinforces the adaptive potential of this genus, in addition to the seasonal exploration of prey in highly disturbed environments.